A Methods study on the manufacture of wire rope - Blanco, Jose Marcelo; Dy, Daniel; Javier, Jonamelle; Manuela, Bubut; Mendiola, Lourdes; Monton, Aileen (College of Engineering, 1988)
We have conducted a methods study on the manufacture of Yellow Strand Rope by Jardine Nell and have made recommendations based on our observations. If implemented, the following will be the result : 1. Productivity may be increased by a minimum of 20 percent. 2. Ineffective and inefficient time may be reduced by a minimum of 26 percent. 3. The layout may be altered in order to facilitate a smoother flow of production. 4. More precautions may be installed to ensure the safety of each worker.